Biomechanics sensor nodes for body tracking: a development solution for virtual reality interaction - Ribeiro, Elvis Hernandes; Guimarães, Marcelo de Paiva; Brega, José Remo Ferreira; Brandão, Alexandre Fonseca; Dias, Diego Roberto Colombo (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2021: Anais do XXIII Simpósio de Realidade Virtual e Aumentada, 2021)
In recent years virtual reality has become increasingly present in areas such as Healthcare, for example, in supporting the neuromotor rehabilitation process of patients. Virtual reality in the health area has been used in various ways. It is a tool to encourage patients to increase their commitment to the rehabilitation sessions. However, despite the hardware and software advances in recent years, there is still a lack of tools to facilitate new virtual reality applications development, especially those using body tracking sensors. This article presents the BSNAsset, a development solution that facilitates new virtual reality applications that use body tracking sensors, such as the Biomechanics Sensor Nodes.